Transgressive tales : queering the Grimms - Turner, Kay, 1948-; Greenhill, Pauline (Series in fairy-tale studies., 2012)
The stories in the Grimm brothers' Kinder- und Hausmärchen (Children's and Household Tales), first published in 1812 and 1815, have come to define academic and popular understandings of the fairy tale genre. Yet over a period of forty years, the brothers, especially Wilhelm, revised, edited, sanitized, and bowdlerized the tales, publishing the seventh and final edition in 1857 with many of the sexual implications removed. However, the contributors in this book demonstrate that the Grimms and other collectors paid less attention to ridding the tales of non-heterosexual implications and that, in fact, the Grimms' tales are rich with queer possibilities. The editors introduce the volume with an overview of the tales' literary and interpretive history, surveying their queerness in terms of not just sex, gender, and sexuality, but also issues of marginalization, oddity, and not fitting into society. In three thematic sections, contributors then consider a range of tales and their queer themes. In Faux Femininities, essays explore female characters, and their relationships and feminine representation in the tales. Contributors to Revising Rewritings consider queer elements in rewritings of the Grimms' tales, including Angela Carter's The Bloody Chamber, Jeanette Winterson's Twelve Dancing Princesses, and contemporary reinterpretations of both 'Snow White' and 'Snow White and Rose Red.' Contributors in the final section, Queering the Tales, consider queer elements in some of the Grimms' original tales and explore intriguing issues of gender, biology, patriarchy, and transgression. -- Publisher's description.